Conveyor Line Development Features for Pharmaceutical Products Industrial Logistics - Nevliudov, I; Yevsieiev, V; Maksymova, S; Klymenko, O (ISMA, 2024)
This section of the monograph examines the key stages of designing and creating an automated sorting system in the pharmaceutical industry. The main focus is on developing the scheme and selecting the supporting modules for assembling the line layout, as well as creating a control system based on the Siemens S7-1200 programmable logic controller (PLC). The work presents detailed photographs of the assembled layout, which allows visualizing the final design result. In addition, an electrical circuit for connecting the PLC, a functional diagram for connecting the conveyor sections, and a plan for their placement have been developed and presented, wich ensures a comprehensive understanding and implementation of the project for automating sorting processes in the pharmaceutical industry.
Keywords: automated sorting system; pharmaceutical industry; automating sorting processes